MEMAKNAI "AMANAH" ATAS PRAKTIK AKUNTABILITAS PADA ORGANISASI AMIL ZAKAT NURUL HAYAT SURABAYA - Vidya Agustinawati; Rizal Mawardi (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2018)
Zakat, Infak, Sedekah (ZIS) management institutions as one way of balancing social economy with equal distribution of income but a crisis of confidence due to the lack of accountability practices through financial reporting and service-based Information Technology (IT) in modern era. The purpose of this study reveals how accountability practices can increase public awareness to fulfill Zakat, Infaq and Sedekah (ZIS) as well as to influence the behavior of ZIS managers in presenting reports on Zakat acceptance as a form of accountability and channeling their funds to achieve social welfare through the Education Scholarship Program. The method used is case study at Lembaga Amil Zakat Nasional Nurul Hayat Foundation, Surabaya. Sources of data in this study are primary data and secondary data. Data collection techniques are conducted by: 1) Direct Observation, 2) Interviews, and 3) Documentation. The analysis of data to be performed consists of description and content analysis. The collected data was then analyzed using descriptive method, with qualitative analysis. The first finding of this study is the practice of Accountability based on Islamic Sharia has brought consequences that the humanitarian aspect of zakat accounting, that is related to the implementation of moral ethical principles and God's law. Another finding obtained by researchers is on Zakat online payment system "ZakatKita". The management of ZIS Nurul Hayat has developed because this online system makes it easier for the muzakki, donators to do Zakat, Infak, Sedekah wherever they are and whenever want to do it. Keywords – amil zakat organitation, amanah, accountability practice, zakat, infaq dan sedekah (ZIS)